EVALUASI PENERAPAN RENCANA PEMBELAJARAN SEMESTER (RPS) PADA PROGRAM STUDI MANAJEMEN IAIN KERINCI - Pebi Julianto; Samin Samin; Faizin Faizin (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2022)
Abstract Semester Learning Plan (RPS) is a plan for the process of learning activities in courses that are prepared by the lecturer independently for one semester. As a professional, every speaker must have certain abilities in order to carry out his duties as a speaker as well as possible. The purpose of this research is to find out the constraints of the lecturers of the Da'wah Management Study Program FUAD IAIN Kerinci in making the RPS, to find out the extent to which the institution holds training or workshops providing workshops for lecturers, to find out the steps that must be taken by the lecturers of the Da'wah Management Study Program at FUAD IAIN Kerinci so that the RPS can be collected at the beginning of each semester. The approach used in this research is a qualitative approach, meaning the procedure (path) in which research is carried out systematically which is used to examine or study an object in a natural setting without any manipulation in it and without any hypothesis testing. The object of this research is the Lecturer of the Da'wah Management Study Program, Faculty of Ushuluddin, Adab and Da'wah, the State Islamic Institute of Kerinci. RPS made by lecturers have been able to accommodate students to be able to study actively and independently. The RPS has been equipped with various components such as competencies, course descriptions, credit scores, lecturers, module topics, learning experiences, educational media, learning resources, to the assessment criteria used. Keywords: evaluation; RPS; learning process Abstrak  Rencana Pembelajaran Semester (RPS) merupakan  rencana proses kegiatan pembelajaran pada mata kuliah yang disusun oleh dosen secara mandiri untuk satu semester. Sebagai seorang profesional, setiap pembicara harus memiliki kemampuan tertentu agar dapat menjalankan tugasnya sebagai pembicara dengan sebaik-baiknya. Tujuan dari penelitian ini adalah Untuk mengetahui kendala dosen Prodi Manajemen Dakwah FUAD IAIN Kerinci dalam pembuatan RPS, Untuk mengetahui sejauh mana Institusi mengadakan pelatihan atau workshop penyediaan workshop bagi dosen, Untuk mengetahui langkah-langkah yang harus dilakukan dosen Prodi Manajemen Dakwah FUAD IAIN Kerinci sehingga RPS bisa terkumpul disetiap awal semester. Pendekatan yang digunakan dalam riset ini adalah pendekatan kualitatif, maksudnya tata cara (jalur) dimana riset yang dilakukan secarasistematis yang digunakan untuk mengkaji ataupun mempelajari sesuatu objek pada latar alamiah tanpa terdapat manipulasi didalamnya serta tanpa terdapat pengujian hipotesis. Objek penelitian yang diteliti adalah Dosen Program Studi Manajemen Dakwah Fakultas ushuluddin, Adab dan Dakwah Institut Agama Islam Negeri Kerinci. RPS yang terbuat oleh dosen telah bisa mengakomodir mahasiswa agar mampu belajar secara aktif serta mandiri. RPS telah dilengkapi dengan berbagai komponen-komponen seperti kompetensi, deskripsi mata kuliah, bobot SKS, dosen pengampu, topik modul, pengalaman belajar, media pendidikan, sumber belajar, hingga pada kriteria penilaian yang digunakan.Kata Kunci : evaluasi; rencana pembelajaran semester (RPS); proses pembelajaran